(untitled) (IITM Journal of Business Studies, 2024)
Women Self Help Groups are impending in a big way where the spirit of their entrepreneurial capabilities can be transparently witnessed. This research attempted to lay down certain management expertise to the pool of occupations by the women self help groups by creating a space of opportunities to them so that there is a steady growth in the economy. Based on the concept of bi-directional study and purposive sampling design; fifty (50) Women SHGs engaged in preparation of ethnic food items and ten (10) organizations has been considered by the researcher. The study area has been confined to the Sivasagar District of Assam. The study emphasized on the nature of the SHGs operations and highlighted the characteristics of the ethnic food items that can be incorporated in a ready to eat ethnic lunch basket. Competitiveness of the ethnic food items of the SHGs in the competitive market has also been put forward by the researcher through an effective cost feasibility analysis. Suitable marketing, positioning & branding strategies of the ethnic food items and the selection of an effective distribution channel for the SHGs has also been proposed by the researcher. From the study, it was inferred that the women members of the SHGs can enter into the competitive market with a boom and with effective promotional & positioning strategies, the ethnic food items of Assam do posses the capacity of giving stiff competition to the commercial food items and can create a niche in the market and thus, can also attain a national presence.